Human resource officers perception of industrial revolution 4.0 in human resource practices and performance - Siti Nurhidayah, Ismail (2020)
Based on the theory of planned behaviour and related literature review, this study empirically investigates the perception of human resource officers in Industrial Revolution 4.0 while implementing their human resource practices; to know how human resource officers change and adapt in Industry Revolution 4.0. Research design using quantitative method was used to analyse data obtained from respondents from banks that operate in the northern region. Consistent with the four hypotheses deducted in this study, results confirmed in the first place that the emergence of Industrial Revolution 4.0 have positively affected the productivity of human resource management. Industry 4.0 is still under the process of evolution as the technologies are still in the development stage. The level of acceptance and adaptation of human resource officers behave to the new IR 4.0 are under this study concern. The key findings in this study showed that there is a significant relationship between human resource officers’ perception of Industrial Revolution 4.0 in recruitment, performance appraisal, compensation and benefits with human resource officers’ performance. While there is no significant relationship between human resource officers' perceptions of Industrial Revolution 4.0 in training and development with the performance of human resource officers. Therefore, hypotheses 2, 3 and 4 are accepted while hypothesis 1 is rejected.